Manajemen Sebagai Sains, Seni dan Profesi Serta Implementasinya di UPTD SD Negeri 03 Muaro Paiti - Yuher Lona, Efni; Arisman, Arisman (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2025)
Management is a systematic and structured process that integrates aspects of planning, organizing, implementing, controlling and evaluating to achieve main goals. This research was conducted at UPTD SD Negeri 03 Muaro Paiti, with the aim of describing management implementation at this institution. The approach used is qualitative research with analytical descriptive methods, using data collection techniques through observation, interviews and documentation. The results of the research reveal that the leadership of the UPTD principal of SD Negeri 03 Muaro Paiti, since its founding until now, has mostly applied the concept of management as an art. . This is caused by the absence of a formal or professional educational background in the field of management among the serving school principals. Replacement of school principals is based more on family factors, which then have an impact on the quality of school management and the achievement of the institution's goals